2022
DOI: 10.1371/journal.pgen.1010190
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the mitochondrial exonuclease MGME1 develop inflammatory kidney disease with glomerular dysfunction

Abstract: Mitochondrial DNA (mtDNA) maintenance disorders are caused by mutations in ubiquitously expressed nuclear genes and lead to syndromes with variable disease severity and tissue-specific phenotypes. Loss of function mutations in the gene encoding the mitochondrial genome and maintenance exonuclease 1 (MGME1) result in deletions and depletion of mtDNA leading to adult-onset multisystem mitochondrial disease in humans. To better understand the in vivo function of MGME1 and the associated disease pathophysiology, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…The preference for a 5′-phosphate may be an important factor in regulating the activity of MGME1 to cooperate with the 3′–5′ exonuclease activity of pol γ in degrading linear mtDNA ( 32 ). In addition, MGME1 has also been proposed to remove flaps formed when mtDNA replication is reaching completion ( 20 , 23 ). The preferential processing of flaps from the 5′-end would facilitate the formation of ligatable ends, which are necessary for the completion of mtDNA replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preference for a 5′-phosphate may be an important factor in regulating the activity of MGME1 to cooperate with the 3′–5′ exonuclease activity of pol γ in degrading linear mtDNA ( 32 ). In addition, MGME1 has also been proposed to remove flaps formed when mtDNA replication is reaching completion ( 20 , 23 ). The preferential processing of flaps from the 5′-end would facilitate the formation of ligatable ends, which are necessary for the completion of mtDNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…The superfamily includes a variety of enzymes involved in DNA and RNA cleavage. MGME1 interacts with all three components (POLG, SSBP1, and TWNK) of the minimal mitochondrial replisome ( 18 , 19 ) and therefore is considered a component of the mitochondrial replication machinery ( 20 ). MGME1 has a documented role in maintaining 7S DNA ( 11 , 17 , 18 , 21 ).…”
mentioning
confidence: 99%
“…Similarly, the polymerase gamma (PolG) deficient 'mutator' mouse model of mtDNA instability has been shown to have aberrantly hyperactive innate immune responses, with type-I interferon responses contributing at significantly to the phenotype [120]. In a more recent third model of mtDNA instability, loss of the mitochondrial genome maintenance exonuclease Mgme1, which causes adult-onset mitochondrial disease in humans, results in severe autoimmune disease with prominent inflammatory renal disease [121]. Infiltrating T-and B-cells were present in these renal lesions, and elevated levels of circulating blood IL-6, TNFα, IL-10, and IL-2 indicating systemic inflammation.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…A decrease in mtDNA content was the main cause of reduced OXPHOS in chromophobe renal cancer (ChRCC) [ 96 ]. The latest study showed that mtDNA replication defects led to the formation of mtDNA linear deletion, which triggered an immune response and led to progressive kidney disease in aging animals [ 97 ].…”
Section: Mtdna Damage In Kidney Diseasesmentioning
confidence: 99%